DNA BARCODING OF THE PENINSULAR INDIAN MEMBERS OF THE BLACK FLIES (SIMULIUM: SIMULIIDAE: DIPTERA) - VEERANARAYANAN SURYA AATHMANATHAN,; SANKARAPPAN ANBALAGAN,; MUTHUKALINGAN KRISHNAN, (The Bioscan, 2020)
We examined the efficiency of DNA barcoding gene (cytochrome oxidase subunit I) for differentiating morpho- species and cytoforms of black fly species (subgenus, Gomphostilbia) complexes reported in India and analyzed their relationship with members found in South-East Asian countries. Results shows that the spatial heterogeneity is an important factor for determining the diversity of species. The phylogenetic trees derived from DNA barcodes grouped for selected taxa according to species recognized by morpho-taxonomic studies. Inter-specific sequence divergences within morphologically distinct species ranged from 0.66 to 0.99%, while higher divergences (73 to 78%) in species complexes suggest the presence of genetic diversity. DNA barcoding combined with a rigorous morpho-taxonomic context given an effective method for identification and phylogenetic relationship of black flies.